Varroa destructor and viruses association in honey bee colonies under different climatic conditions - Giacobino, Agostina (2016)
Honey bee colonies are threatened by multiple factors including complex interactions between environmental and diseases such as parasitic mites and viruses. We compared the presence of honeybee-pathogenic viruses and Varroa infestation rate in four apiaries: commercial colonies that received treatment against Varroa and non-treated colonies that did not received any treatment for the last 4 years located in temperate and subtropical climate. In addition, we evaluated the effect of climate and Varroa treatment on deformed wing virus (DWV) amounts. In both climates, DWV was the most prevalent virus, being the only present virus in subtropical colonies. Moreover, colonies from subtropical climate also showed reduced DWV amounts and lower Varroa infestation rates than colonies from temperate climate. Nevertheless, non-treated colonies in both climate conditions are able to survive several years. Environment appears as a key factor interacting with local bee populations and influencing colony survival beyond Varroa and virus presence.